Strategic visualization: the (real) usefulness of cognitive mapping in smart city conceptualization - Vaz, A.; Ferreira, F.; Pereira, L.; Correia, R.; Banaitis, A. (Management Decision, 2022)
Purpose – The concept of smart city has recently becomemore topical in academic and policy discussions. This idea is considered a complex, non-consensual subject since its definition has not yet been agreed upon by most authors in the relevant fields. The need to identify and measure smart city indicators has also given rise to many different evaluation procedures. However, the available frameworks have yet to overcome challenges in structuring and measuring all the evaluation parameters of the cities in question. Thus, methods still need to be developed and applied that can structure criteria used to assess smart city success. Design/methodology/approach – This study sought to show cognitive mapping’s tangible usefulness as an expedient tool for strategic analysis, using smart cities as a complex object of study. To this end, various cognitive maps were constructed and compared using the Strategic Options Development and Analysis (SODA) approach. Findings – Cognitive mapping’s advantages and limitations in the strategic visualization research context are analyzed and discussed. Originality/value – The authors know of no prior work reporting comparative analysis of this methodological approach in the same research context.